Usral (E. Radigue) - Parra Cancino, Juan; Orpheus Live Series Koetshuis Orpheus Institute 27 June 2024 (2023)
Modular Synthesizer
Performance of Éliane Radigue's "Usral", as part of the Orpheus Live series.
FRIS
Editorial review
Keywords: Music, Thought and Technology